Telomere in Aging and Age-Related Diseases - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Indonesian Biomedical Journal, 2017)
BACKGROUND: The number of elderly population in the world keep increasing. In their advanced ages, many elderly face years of disability because of multiple chronic diseases, frailty, making them lost their independence. Consequently, this could have impacts on social and economic stability. A huge challenge has been sent for biomedical researchers to compress or at least eliminate this period of disability and increase the health span.CONTENT: Over the past decades, many studies of telomere biology have demonstrated that telomeres and telomere-associated proteins are implicated in human diseases. Accelerated telomere erosion was clearly correlated with a pack of metabolic and inflammatory diseases. Critically short telomeres or the unprotected end, are likely to form telomeric fusion, generating genomic instability, the cornerstone for carcinogenesis. Enlightening how telomeres involved in the mechanisms underlying the diseases’ pathogenesis was expected to uncover new molecular targets for any important diagnosis or therapeutic implications.SUMMARY: Telomere shortening was foreseen as an imporant mechanism to supress tumor by limiting cellular proliferative capacity by regulating senescence check point activation. Many human diseases and carcinogenesis are causally related to defective telomeres, asserting the importance of telomeres sustainment. Thus, telomere length assessment might serve as an important tool for clinical prognostic, diagnostic, monitoring and management.KEYWORDS: telomerase, cellular senescence, aging, cancer